Antioxidant, anti-inflammatory, and anti-apoptotic efficacy of pomegranate molasses versus peel extract against sodium nitrate hepatotoxicity in rats - Khalifa, Hanem K.; Tahoun, Enas A.; Masoud, Shimaa R.; Mady, Rehab (Journal of Advanced Veterinary Research, 2025)
The current research was performed to compare the efficacy of pomegranate molasses (PM) versus pomegranate peel aqueous extract (PPAE) in ameliorating the hepatotoxicity of sodium nitrate. The phytochemical screenings of PM and PPAE were analyzed using GC/MS. Sixty male rats were randomly assigned to six equal groups and treated for 10 successive weeks. The control group received distilled water orally, the PM and PPAE groups were orally administered PM (0.5 ml/rat) and PPAE (100 mg/kg), respectively, the nitrate group received sodium nitrate (500 ppm) in drinking water, the Nitrate+PM and Nitrate+PPAE groups received PM and PPAE, respectively with nitrate. Sodium nitrate-intoxicated rats showed significant elevations in the activities of serum alanine aminotransferase and aspartate aminotransferase, significant increases in malondialdehyde, nitric oxide, and hydrogen peroxide levels, as well as significant decreases in reduced glutathione content and catalase activity in hepatic tissues. Moreover, sodium nitrate caused histopathological alterations in the liver, along with significant increases in the expressions of caspase-3, Bax, Bax/Bcl-2 ratio, tumor necrosis factor α, and glial fibrillary acidic protein and decrease in B-cell lymphoma-2 expression. Conversely, the concomitant administration of either PM or PPAE with sodium nitrate mitigated the biochemical, histopathological, and histochemical toxic effects induced by sodium nitrate intoxication. Accordingly, pomegranate molasses and peel extract exhibited similar protective effects against sodium nitrate-provoked hepatotoxicity, mainly via their antioxidant, anti-apoptotic, and anti-inflammatory activities.